Mendorong Terciptanya Masyarakat Inklusif dengan Pelatihan Bahasa Isyarat Tingkat Dasar di Kampung Jonasan, Pucangsawit, Surakarta - Cucuk Wawan Budiyanto; Syah Bilal Ahtafiand; Dian Pertiwi Agustin; Gangga Santika Alvidya Putri Refindra; Katryn Monica Zalimov; Muna Yazidatul Falihah; Dita Rofika Cahyani; Gabriela Kusuma Wardani; Bella Windira Sari; Dwi Novi Aldiyanto; Aliyatus Sholihah (DEDIKASI: Community Service Reports, 2025)
People with special needs are often marginalized from society. Barriers to communication make it difficult for people to understand and hinder their participation in their activities. Similar problems were found in KKN activities in Jonasan, Pucangsawit Village. Residents who have special needs, namely deaf disabilities, are considered unable to speak. Observations on conditions in the field indicate the ability to communicate by capturing lip movements, so one of the UNS Group 34 KKN work programs in 2023 conducts basic sign language training for the community. This activity aims to equip the community with understanding and sign language skills at the basic level to become a bridge of communication between Jonasan Village residents and Deaf friends who also live in Jonasan Village. In addition, it is also intended to mitigate the communication gap between residents and people with disabilities, deafness, and similar cases in the community.